METODE ECONOMIC PRODUCTION QUANTITY DALAM SISTEM PERENCANAAN DAN PENGALIHAN PRODUKSI - Yoga Prastya; Tri Irawati; Bambang Satrio Nugroho (STMIK Sinar Nusantara, 2019)
Over Production and developing modes require companies to issue new products before the old product is sold out. The company problem is that the company loses and many products are damaged so the product cannot be sold because the product is stored too long and the storage costs and selling value fall product because of similar product competition. The product control phase began to be implemented to anticipate the swelling of new inventories, with the method of economic production quantity being one of the efforts to suppress production and control production so that the value of these products could be maintained and the company would not suffer losses due to damage to manufactured goods. Types of Data consist of Primary Data, There are 2 kinds of primary data that the authors do, namely: Observation Method, Interview Method, and Secondary Data in the form of Library Studies Browsing the Internet. Data analysis by analyzing the system using UML, input-output design and system testing From another process, one form of a separate data collection process is provided according to the production data control needs of the EPQ Method and is feasible if the process is stored in full. And the data displayed is in accordance with the testing of Production control validity and the results of the test can be concluded that the software built is free of syntax errors for results that are as expected. All functions in the production control application with the Algorithm method can be valid.Keywords: Production Control, Pola, Economic Production Quantity